Quantitative, In Situ Visualization of Metal‐Ion Dissolution and Transport Using 1H Magnetic Resonance Imaging. Issue 32 (22nd June 2016) - Bray, Joshua M.; Davenport, Alison J.; Ryder, Karl S.; Britton, Melanie M.
Abstract: Quantitative mapping of metal ions freely diffusing in solution is important across a diverse range of disciplines and is particularly significant for dissolution processes in batteries, metal corrosion, and electroplating/polishing of manufactured components. However, most current techniques are invasive, requiring sample extraction, insertion of an electrode, application of an electric potential or the inclusion of a molecular sensor. Thus, there is a need for techniques to visualize the distribution of metal ions non‐invasively, in situ, quantitatively, in three dimensions (3D) and in real time. Here we have used 1 H magnetic resonance imaging (MRI) to make quantitative 3D maps showing evolution of the distribution of Cu 2+ ions, not directly visible by MRI, during the electrodissolution of copper, with high sensitivity and spatial resolution. The images are sensitive to the speciation of copper, the depletion of dissolved O2 in the electrolyte and show the dissolution of Cu 2+ ions is not uniform across the anode. Abstract : Insights into corrosion processes : Magnetic resonance imaging is used to quanititatively map the distribution of copper(II) ions during the electrodissolution of metallic copper (see picture). The method is non‐invasive and can be applied in situ, in three dimensions, and in real time. The dissolution of Cu 2+ ions is shown to be non‐uniform across the anode.